Analysis of the implementation of the Central Asia water&energy program in the framework of new EU strategy for Central Asia (Халықаралық қатынастар және халықаралық құқық сериясы, 2021)
The recently launched European Union (EU) Strategy for Central Asia is expected to continue activities that were not completed during the implementation of the previous strategy on the basis of already existing successes and achievements, gaps will be filled and cooperation in emerging new areas and spheres will be established. In the framework of the New Strategy, the Central Asia Water & Energy Program (CAWEP) was implemented to help the Central Asian countries strengthen their energy and water security through knowledge exchange, analytical work, policy advice, and project preparation.The article will be focused on the analysis of implementation of the CAWEP in Central Asian states. CAWEP has been implemented since 2009. Therefore, there are goals reached successfully and projects that need to be worked on further. The article will discuss how the program is being realized in each Central Asian state and what actions have already been done under the program.Key words: CAWEP, Central Asia, European Union, World Bank.